Тенденції розвитку та перспективи активізації збуту суб’єктів страхового ринку України - Кузьо, Н. Є.; Косар, Н. С.; Kuzo, N. Ye.; Kosar, N. S. (Видавництво Львівської політехніки, 2022)
Дослідження свідчать, що протягом 2018–2021 рр. спостерігалися позитивні зрушення на ринку страхових продуктів України щодо основних показників його розвитку. Проте в умовах пандемії, воєнного стану суттєво змінилися умови функціонування вітчизняних страхових компаній, внаслідок чого вони оновили пропонований асортимент своїх продуктів. Також зросло значення їх реалізації онлайн, зокрема з використанням мобільного додатку. Він найчастіше використовується щодо продуктів страхування майна з високою частотою дрібних пошкоджень. Визначено, що сьогодні мобільні додатки для збуту страхових продуктів використовує лише невелика кількість страховиків, і вони мають обмежену кількість функцій. Рекомендованими основними функціями мобільного додатку страховика є: пошук інформації клієнтом; придбання страхового продукту; обслуговування страхових полісів та їх поновлення; врегулювання страхового випадку; обслуговування збитків.

Research shows that during 2018–2021, positive changes were observed in the market of insurance products in Ukraine, although the number of insurance companies has constantly decreased in recent years. The conducted analysis enabled a trend toward the growth of net insurance premiums and net insurance payments in Ukraine. However, in the pandemic, the operating conditions of domestic insurers have changed significantly, as a result of which they have improved existing insurance programs, introduced new insurance products to the market, and organized online sales of their products – the importance of the latter increases in the conditions of martial law. Taking into account that the use of mobile devices is multiplying in Ukraine, developing and using a suitable mobile application is an urgent direction for activating activities in the field of sales for insurance companies. It is most commonly used for property insurance products with a high frequency of minor claims. It was determined that today mobile applications are used for the sale of insurance products by such companies as “UNIQA Insurance Group” PJSC, “Ingo Ukraine” PJSC, “Knyazha Vienna Insurance Group” PJSC, “Greenwood Life Insurance” LLC, “Ukrainian joint-stock insurance company «Aska»” PJSC and PrJSC “Insurance company «ARX»”. The article analyzes their primary functions. Existing applications of insurance companies on the Ukrainian market help their clients to obtain operational information about current insurance contracts, calculate the cost of a new insurance contract, make an online payment of the insurance premium, make an appointment with a doctor, and upload personal documents for insurance payment. The recommended main functions of the insurer’s mobile application are information search, purchase of an insurance product, maintenance of insurance policies and their renewal, insurance claim settlement, and maintenance of damages. Other long-term trends in the innovative activities of insurance companies in sales policy are the formation of a “multi-channel” system of interaction with customers and rewards for customer loyalty, reduction of the insurance company’s response time to customer requests, provision of high-quality and fast service through the use of IT technologies and modernization of business processes.
Development tendencies and prospects for the activation of sales of entities in the insurance market of Ukraine
Keywords: ринок страхових продуктів; страхові премії; страхові виплати; пандемія; мобільний додаток; цифрові технології; інновації; збутова політика; онлайн-продаж; market of insurance products; insurance premiums; insurance payments; pandemic; mobile applications; digital technologies; innovation; sales policy; online sales; 368.1; 658.8